Anal intraepithelial neoplasia in HIV positive people. Issue 5 (1st October 2001) - Martin, Fabiola; Bower, Mark
Abstract : Objective: To review the current literature on HIV associated anal intraepithelial neoplasia (AIN). Methods: A comprehensive Medline/Pubmed search was performed for the years 1980–2001 (January) for articles pertaining to HIV associated anal intraepithelial neoplasia. From the MeSH terms "anal intraepithelial neoplasia" and "anal cancer" the following subheadings were used: HIV, homosexual men, HPV, Epidemiology, Etiology, Mortality, Diagnosis, Screening, Drug Therapy, Surgical Therapy, Radio Therapy, Risk factors, ASIL. The search was limited to "human" for all searches. In the absence of enough "randomised controlled trials" the search was extended to clinical trials, reviews, and case reports. One analysis on cost effectiveness and two abstracts presented at 12th World AIDS Conference and 6th Conference on Retrovirus and Opportunistic Infections were included. The 44 publications referred to originate from the United Kingdom (9), the United States (26), and Denmark (5), with one each from Switzerland, Germany, Australia, and France. The Cochrane Database of systematic reviews yielded 11 complete reviews for "anal cancer" and none for "anal intraepithelial neoplasia." The textbook of AIDS-related cancers and their treatment was consulted. We also included our personal experience from the treatment of patients at the Chelsea and Westminster Hospital, one of the largest centres for the management of HIV disease in Europe. Conclusion: Routine anal cytological screening followed by appropriate management of AIN is an important issue for HIV infected patients. The natural history of AIN has not been fully established and this prevents clinicians from defining clear management protocols. There is early evidence that the benefits of highly active antiretroviral therapy (HAART) in terms of restoring immune function and reducing opportunistic infections and some neoplasms may not extend to regression of AIN. Under these circumstances it might be predicted that AIN and subsequent progression to invasive anal cancer would rise as HAART prolongs the lives of seropositive people. However, routine anal cytological screening will surely have to await an effective proved intervention for AIN and this would seem to be a pressing clinical goal. Sex Transm Inf (Sex Transm Inf 2001;77 :327–331)